EFL Learners’ Literacy with and Without ER in Reading English - Rahmawati, Henny; Mazhabi, Zobi (Universitas Negeri Malang, 2020)
This study aimed at exploring the students’ beliefs towards reading between those who have followed ER and those who have not in the distinct level of reading ability—high, intermediate, and low level. This present study was a qualitative study concerning the students’ perception towards a particular issue. The findings show that the students’ beliefs towards reading English, for those who have followed ER with a high level of competency, remains the same as intensive reading principles. While, unexpectedly, those who have not yet followed ER at the same level have some beliefs which refer to ER principles. For the intermediate and low level for either those who have or have not yet followed ER, their principles remained the same reflecting those of intensive reading. This study contributes practically to ER practitioners in implementing ER in order that ER, within classroom activities, can run as it is by minimizing the biases and maximizing its benefits based on the outcomes, the students’ beliefs towards reading in English. Theoretically, the contribution lies at an additional confirmation that the outputs of ER, in the form of students’ beliefs, may result unexpectedly for many factors contributing to its success must really be well-monitored. The conclusion and suggestions are then attached to the end of this paper.